OP0185 KNEE JOINT DISTRACTION IS MORE EFFICIENT IN RESTORING CARTILAGE THICKNESS THAN HIGH TIBIAL OSTEOTOMY IN PATIENTS WITH SEVERE KNEE OSTEOARTHRITIS. (2nd June 2020) - Jansen, M.; Maschek, S.; Van Heerwaarden, R.; Mastbergen, S.; Wirth, W.; Lafeber, F.; Eckstein, F.
Abstract : Background: Both high tibial osteotomy (HTO) and knee joint distraction (KJD) are joint preserving surgical techniques unloading the affected femorotibial compartment in patients with knee osteoarthritis (OA). While HTO permanently unloads the more affected compartment (MAC) by overcorrecting the leg axis, KJD temporarily unloads the whole joint by separating the tibia and femur for 5 mm for 6 weeks. In a previous randomized controlled trial (RCT), comparable clinical benefit and radiographic joint space width (JSW) increase over 2 years follow-up were demonstrated for both treatments 1 . Yet, comparison of JSW before and after HTO may be unreliable, as pseudo-widening of the unloaded compartment may occur due to the induced leg axis change. Therefore, direct cartilage thickness measurements need to be compared between KJD and HTO, to accurately evaluate the efficacy of both treatment options on cartilage structure. Objectives: To compare two-year cartilage thickness changes after treatment with KJD vs HTO and identify factors predicting cartilage thickness restoration. Methods: Patients indicated for HTO were randomized to KJD (KJDHTO ) or HTO treatment. Patients indicated for total knee arthroplasty received KJD (KJDTKA ). Standardized semi-flexed weight-bearing radiographs and 3T MRIs with 3D spoiled gradient recalled imaging sequence with fat suppression (SPGR-fs) were acquired before and two years after surgical treatment. Cartilage thickness in the knee was measured using Chondrometrics Works 3.0 software. On the radiographs the mean JSW in the MAC were measured with KIDA software. Readers were blinded to the type of intervention and acquisition order. The primary and secondary outcomes were the mean MAC cartilage thickness (ThCtAB) and percentage of denuded bone area (dABp) change before and two years after treatment (MRI), with radiographic joint space width (JSW) used as a reference. Results: No statistically significant differences in the baseline characteristics were seen between KJDHTO (n=18) and HTO (n=33). The KJDTKA group (n=18) had a higher age and Kellgren-Lawrence grade (KLG) than the HTO and KJDHTO groups. KJDHTO patients did not show significant changes in MAC cartilage thickness, dABp, or JSW over time (all p>0.10; figure 1 ). HTO patients displayed a decrease in MAC cartilage thickness and an increase in dABp (both p<0.03), but an increase in JSW (p=0.006). KJDTKA showed a significant increase in MAC cartilage thickness and JSW and decrease in dABp (all p<0.01). Baseline OA severity was the strongest predictor of cartilage restoration. KJD patients with severe OA (KJDsevere ; KLG ≥3) showed significant restoration (all p<0.01; figure 2 ); mild OA patients (KJDmild ; KLG ≤2) showed a slight deterioration. KJDsevere showed a significantly greater cartilage restoration response in the MAC than HTOsevere for cartilage thickness (p=0.005) and dABp (p=0.003), but not JSW change (p=0.521). The changes in all three parameters did not differ significantly between KJDmild and HTOmild (all p>0.08). Conclusion: In patients with severe knee OA, KJD is more efficient in restoring cartilage thickness than HTO is. In these patients, KJD causes significant cartilage restoration while HTO, despite shifting the leg axis and demonstrating radiographic joint space widening, shows loss of cartilage as measured on MRI. In patients with mild knee OA, neither HTO nor KJD treatment results in significant cartilage restoration and both treatments show a slight deterioration that is likely the result of natural OA progression. As such, this research promotes the choice KJD as joint-preserving surgery in case of knee OA patients with more severe structural damage. References: [1]MP Jansen et al, Cartilage 2019. Disclosure of Interests: Mylène Jansen: None declared, Susanne Maschek Shareholder of: Stock/stock options at Condrometrics GmbH, Employee of: Employment at Condrometrics GmbH, Ronald Van Heerwaarden: None declared, Simon Mastbergen: None declared, Wolfgang Wirth Shareholder of: Stock/stock options at Condrometrics GmbH, Consultant of: Consultancy to Galapagos NV, Employee of: Employment at Condrometrics GmbH, Floris Lafeber Shareholder of: Co-founder and shareholder of ArthroSave BV, Felix Eckstein Shareholder of: Stock/stock options at Condrometrics GmbH, Consultant of: Consultancy at Merck KGaA, Samumed, Bioclinica, Galapagos, Servier, Novartis, Employee of: Employment at Condrometrics GmbH, Speakers bureau: Development of educational presentations for Medtronic